Moroccan Migration Dynamics - Rob van der Erf; Liesbeth Heering (United Nations, 2002)
This report by the Netherlands Interdisciplinary Demographic Institute (NIDI) focuses on migration dynamics between Morocco and the European Union. Based on an extensive survey of 2,500 Moroccan households in five provinces in Morocco as well as in five Spanish regions, the study analyses the reasons for migration and identifies social, economic and regional policy issues that need to be addressed in order to moderate the existing migration pressure.